IPO Pricing with Bookbuilding and a When-Issued Market - Alex Stomper; Wolfgang Aussenegg; Pegaret Pichler (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper examines the German IPO pricing process which combines bookbuilding with a liquid pre-IPO when-issued market. We find no partial adjustment phenomenon, as has been documented for U.S. IPOs. We thus find no evidence that bookbuilding provides information for IPO pricing, beyond the information that is required to set preliminary price ranges. Once price ranges are set, when-issued trading commences and indicates how IPOs should be priced in the primary market. However, the evidence suggests that such trading does not fully supplant information gathering through bookbuilding.
Keywords: G32; 330; Initial public offerings; Bookbuilding; When-issued trading; Börsengang; Emissionskurs; Deutschland